Magical Touch of Marketing: Matching Promotion with the 4 R’s of Place Branding. - Mariutti, Fabiana (Archives of Business Research, 2015)
Place marketing has been an object of study since the 1960s; however, even though in the last two decades there has been an increase in research, there is a lack of studies about ‘magic’ in promoting a place because it is a critical topic and an under theorised construct in academia, in general. Debate continues about the marketing strategies and campaigns because of not only the outcomes of continued use of promotional activities of place marketing but also because of the influential aspect of such activities towards emergent countries or cities. The purpose of this paper is to match the P for Promotion from the Marketing Mix model (McCarthy, 1964) with the 4 R’s of the Place Branding model (Aitken & Campelo, 2011) - in order to convey a suggested guideline for the creation of activities in a national park setting. This qualitative research is exploratory in nature, undertaking secondary data collection and content analysis for data interpretation. This paper provides not only awareness of the inappropriate promotion of particular places but also contributes to existing knowledge of place branding literature by providing an understanding of promotion as a potential communication and marketing force – if using appropriate channels and messages – perhaps with a ‘magical’ touch.